Short term effect of virtual reality on tear film stability and ocular discomfort - Sidik Ahmad, Mohamad Syarifuddin; Che Azemin, Mohd Zulfaezal; Ithnin, Mohd. Hafidz; Mohd Tamrin, Mohd Izzuddin (RMP Publications, 2020)
Virtual reality (VR) has been integrated and used with smartphones as one of the digital entertainments such as in gaming and movie streaming. With emergent of various VR brands in the market, it concerns the public on the possible side effects of VR on the ocular performance specifically on tear film stability and ocular discomfort. The purpose of this study was to compare the change on non-invasive keratograph tear break-up time (NIKBUT), tear meniscus height (TMH) before and after the use of VR for 30 minutes, and to measure the ocular discomfort after the use of VR quantitatively. Thirty-two subjects were recruited in this study and all the subjects were divided randomly into two groups; VR and laptop (used as a control) groups. Each subject needed to watch a movie for 30 minutes using the respective devices. The changes of tear film stability and ocular discomfort before and after the use of the devices were then compared and the results showed that there was no significant difference (p>0.05) after 30 minutes of the use. Comparison of the ocular parameters between the devices on post-watching activities was also not significant (p>0.05). Use of VR did not give any signs of dryness to the eyes and it can be used without any discomfort even after 30 minutes usage of the devices.